2021
DOI: 10.1097/md.0000000000024953
|View full text |Cite
|
Sign up to set email alerts
|

MMP7 as a potential biomarker of colon cancer and its prognostic value by bioinformatics analysis

Abstract: Colon cancer is one of the most common cancers in the world. To identify the candidate genes in the carcinogenesis and progression of colon cancer, the microarray datasets GSE10950, GSE44861 and GSE74602 were downloaded from the Gene Expression Omnibus (GEO) database. The differentially expressed genes (DEGs) were identified, and functional enrichment analyses were performed. A total of 176 DEGs were identified, consisting of 55 genes upregulated and 121 genes downregulated in colon cancer tissues compared to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…The FSTL3 expression in CRC was first investigated using the TIMER web tool (https://cistrome.shinyapps.io/timer/) (Li et al, 2017) and the Gene Expression Profiling Interactive Analysis (GEPIA) database (https://www.oncomine.org/) (Tang et al, 2017). The differential expression of FSTL3 was further confirmed using the TCGA-Colon Adenocarcinoma (COAD) cohort and GSE10950, GSE44861 datasets (Zhao et al, 2020;Chen and Ke, 2021).…”
Section: Transcriptomic Expression Analysismentioning
confidence: 99%
“…The FSTL3 expression in CRC was first investigated using the TIMER web tool (https://cistrome.shinyapps.io/timer/) (Li et al, 2017) and the Gene Expression Profiling Interactive Analysis (GEPIA) database (https://www.oncomine.org/) (Tang et al, 2017). The differential expression of FSTL3 was further confirmed using the TCGA-Colon Adenocarcinoma (COAD) cohort and GSE10950, GSE44861 datasets (Zhao et al, 2020;Chen and Ke, 2021).…”
Section: Transcriptomic Expression Analysismentioning
confidence: 99%
“…On the contrary, it has been reported that mice lacking MMP-7 expression have a reduced incidence of colonic adenoma [ 37 ]. In accordance with all of these observations, a recent bioinformatic analysis study based on micro array databases (GSE10950, GSE44861 and GSE744602) identified MMP-7 as the more important gene expression involved in colon carcinogenesis, invasion and recurrence of colon cancer [ 38 ]. This is consistent with the fact that MMP-7 was reported to regulate the occurrence and development of cancer and mediate the proliferation, differentiation, metastasis and invasion of diverse types of cancer cells through various mechanisms (revised by [ 39 ]).…”
Section: Discussionmentioning
confidence: 85%
“…So, they suggested this gene as a drug target for CRC also [ 110 ]. Chen and Ke [ 111 ] detected the gene MMP7 as a potential biomarker of CRC by bioinformatics analysis. Another study found that it regulates cancer progression and mediate the differentiation, proliferation, invasion and metastasis of various cancer cell types by different mechanisms [ 112 ].…”
Section: Discussionmentioning
confidence: 99%